The message of sonship : at home in God's household - Burke, Trevor J. (Downers Grove, Ill. : Inter-Varsity Press, 2011)
"Sonship" is an important, yet often overlooked, theme throughout the Bible. Adam, the first human being, is identified as a "son of God"; Israel is God's "first-born son"; the covenant with King David is cast in father-son terms; Christians are children of God, "adopted as sons"; and the same designation brings Scripture to a triumphant conclusion: "He who overcomes will inherit all this, and I will be his God and he will be my son" (Revelation 21:7). The story line of the Bible makes it clear that God is making for himself a family of sons and daughters who will serve him and reign with him in his kingdom forever- and this purpose is achieved through Jesus Christ, the incarnate Son of God. Trevor Burke shows how "sonship" is the focus of creation, is a metaphor for salvation, carries moral obligation and is the goal of the restoration of broken, suffering humanity.
Introduction : sonship as a Biblical metaphor -- Sonship in the Old Testament -- Sonship in the New Testament.
Includes bibliographical references.
Keywords: Son of God -- Biblical teaching; Children of God -- Biblical teaching; Adoption -- Religious aspects -- Christianity; Metaphor in the Bible; Adoption -- Religious aspects -- Christianity; Children of God -- Biblical teaching; Metaphor in the Bible; Son of God -- Biblical teaching